Smart objects for the industry 4.0 - Vaz, Álvaro Luís de Amorim (2021)
This dissertation was developed in accordance with the present technological context, focusing on the Industry 4.0. The contemporary industrial wave is associated with the rise of diversity and availability of new technologies. With that said is possible to imply that industrial factory efficiency, threw the gathering of information in real time, is even more relevant in today´s society. First aproach to the this disseration was to research what composes a industry 4.0 network the difficulties it is faced with. One of many difficulties observed were the integration of many of physical systems to the cloud while mantaining a reak time feed. Also a system in the industry implies heavy loads in a network therefore there needs be added "lightweight" protocols to run in the system. Following these considerations the company "Körber Supply Chain PT" was contacted. With the idea proposed of using one of their machines a Industrial Internet of Things (IIoT) was developed and tested, aiming that the company would be able access and process machine data in real time while plotting to a dashboard. In this work the processes that compose a network are discussed, with special detail two communication protocols: Message Queuing Telemetry Transport (MQTT) and Advanced Message Queuing Protocol (AMQP). This mentioned protocols are subject to benchmarks made to prove performance and stability of the exposed problem. The parameters tested are the following: maximum message rate, adaptation too node increase and resources used. Upon analyses it was seen that MQTT would be the protocol used. Upon protocol selection follows the system design around the IOT2050 and a Siemens Programmable Logic Controller (PLC). The IOT will function as a Gateway, where the data received by the PLC would be processed to a JavaScript Object Notation (JSON) and then sent to the cloud via MQTT. The IOT2050 will run Node-RED instance with the appropriate ow to accomodate these requirements. Performance test are then made within the context of this dissertation, that prove that the Gateway can keep up with the PLC clock cycles. They also prove that no message is lost between IOT and PLC, although Node-RED may have it´s limitations in generating messages on the 30 millisecond clock cycle. Therefore in the experimental scenario it can be concluded that the system will function in the proposed solution Finally the system was brought to Körber Supply Chain PT warehouse where it was tested on their machine, having the expected results. All variables were read and plotted in the dashboard developed, concluding that the system works in a real life application.